HPTLC Autography Based Screening and Isolation of Mushroom Tyrosinase Inhibitors of European Plant Species. Issue 3 (14th February 2019) - Revoltella, Silvia; Rainer, Bettina; Waltenberger, Birgit; Pagitz, Konrad; Schwaiger, Stefan; Stuppner, Hermann
Abstract: In the course of this project, 133 plants were evaluated on their ability to inhibit tyrosinase, a key enzyme in melanogenesis. The screening was performed by means of a HPTLC autographic assay, resulting in the selection of three plants, Asplenium trichomanes, Pinus uncinata, and Scutellaria altissima, with promising tyrosinase inhibiting activities. With the aid of the HPTLC assay, it was not only possible to select the most interesting plant extracts, but also to monitor the activity‐guided fractionation which, in a relatively short time period, led to the isolation of active principles. Benzoic acid, roseoside, and dihydrovomifoliol‐ O ‐ β ‐d ‐glucopyranoside could be identified as tyrosinase inhibitors present in P. uncinata . Globularin turned out to be the active principle of S. altissima, and 4‐ethenylphenyl 6‐ O ‐(6‐deoxy‐ α ‐l ‐mannopyranosyl)‐ β ‐d ‐glucopyranoside was detected as tyrosinase inhibitor of A. trichomanes . The pure compounds were tested also in a 96 well‐plate assay in order to determine their IC50 values. The lowest IC50 value (42 μm ) could be obtained for globularin, whereas the other compounds, e. g., benzoic acid exhibited a rather high IC50 value (IC50 =552 μm ). This stood in clear contrast to the autographic assay, but is has to be taken into account that the outcome of the autography assay is not only depending on the IC50 value of a compound, but also on the content of the respective constituent in the extract. Abstract :